2019
DOI: 10.1016/j.cyto.2018.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Procalcitonin levels predicting the infliximab response of immunoglobulin resistant Kawasaki disease

Abstract: To search the predictive factors of infliximab resistance in intravenous immunoglobulin (IVIG)-resistant Kawasaki disease (KD) patients. Study design. Twenty-seven patients with KD who received infliximab after 4-5 g/kg of IVIG therapy from 2013 to 2015 were consecutively recruited in this study. They were divided into two groups: patients who responded to infliximab (infliximab-responsive group, n = 15) and patients who required additional therapy for the disease control (infliximab-resistant group, n = 12). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The pre-IVIG regression model showed PCT > 1.81ng/ml before initial IVIG treatment was an independent predictor of repeated IVIG resistance in KD. Comparing with CRP as well as the other inflammation indicator, PCT may reflect uncontrollable hypercytokinemia faster along with the involvement of TNF-α signaling pathway in KD, based on the characteristics of early elevation and shorter half time [23]. Pre-IVIG NT-proBNP yielded the highest specificity, but it failed to predict repeated IVIG resistance, the reason may be due to relatively low sensitivity of 45.00 %.…”
Section: Discussionmentioning
confidence: 99%
“…The pre-IVIG regression model showed PCT > 1.81ng/ml before initial IVIG treatment was an independent predictor of repeated IVIG resistance in KD. Comparing with CRP as well as the other inflammation indicator, PCT may reflect uncontrollable hypercytokinemia faster along with the involvement of TNF-α signaling pathway in KD, based on the characteristics of early elevation and shorter half time [23]. Pre-IVIG NT-proBNP yielded the highest specificity, but it failed to predict repeated IVIG resistance, the reason may be due to relatively low sensitivity of 45.00 %.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have suggested using PCT levels to predict the occurrence of IVIG-resistant KD. Research investigations by Yoshikawa et al 36 , Dominguez et al 37 , Nakashima et al 38 , and Nakamura et al 39 demonstrated that the critical value of PCT for predicting IVIG-resistant KD ranged from 0.5 to 4.3 ng/mL, confirming the crucial role of PCT in drug resistance in KD. In support of this finding, the present study also found that PCT level might serve as a predictor of IVIG-resistant KD at a critical value of 0.845 ng/mL, consistent with the previous studies.…”
Section: Discussionmentioning
confidence: 91%
“…Nakashima et al. ( 71 ) aimed to develop a clinical prediction model for IFX responsiveness in patients with IVIG-refractory KD. Several studies ( 72 , 73 ) proposed procalcitonin as a biomarker to predict the severity of KD.…”
Section: Conclusion and Perspectivementioning
confidence: 99%